Science popularization on Instagram: an initial study based on Information Design analysis - Luna Gomes Ramos, Renata Kelly; Rolim Miranda, Eva; Soares, Mônica (InfoDesign, 2025)
The science popularization on social media has expanded access to knowledge but also intensified misinformation, highlighting the need to adapt scientific knowledge to ensure high-quality information reaches the public. Information Design helps organize complex content into clear and accessible visualizations. This study evaluated the comprehension of eleven non-design participants regarding five posts from scientific profiles on Instagram – four created by researchers without design expertise and one by an institution with a dedicated communication team. The analysis focused on typography, color use, images, and content. Results showed that, even without design training, participants perceived weaknesses in the Information Design of the posts, compromising content reception. The main comprehension difficulties followed a hierarchy: legibility was the most critical factor due to poor text-background contrast and inappropriate typography, followed by visual hierarchy, with a lack of emphasis on key content and differentiation between primary and secondary information. Visual unity was also affected by the lack of standardization in the posts. These findings reinforce the need for greater attention to typography, color, and composition in science communication. The study suggests that scientists adopt Information Design principles or collaborate with specialists, integrate Information Design courses into academic programs, and explore design aspects beyond aesthetics, focusing on the effective organization of information.